The Problem of Increasing of Teachers’ Qualification in Work of Congresses of Teachers in Ukraine (at the End of the XIX Century) - Nataliia Petroshchuk (Pedagogical Discourse, 2014)
It is analyzed in the article that at the end of the XIX century on the Ukrainian land that was part of the Russian empire was lack of qualified teaching staff for public schools. It was found that one of the most effective ways to solve this problem was to hold congresses for teachers to improve their qualifications. Congresses not only taught, but gathered teachers. It was found out that firstly congresses of inspectors of public schools were held and urgent questions of the organization of school life were tackled. Later, in 1880-s, teachers congresses were held, that were addressed to issues of organizing of learning in public schools, improve training and methodological support schools to improve wages and living conditions of teachers. At congresses teachers of public schools used different forms of work for improving their skill level.Pedagogical congresses that time had great social significance, as there was a way to pay public attention to the problems of primary school teachers training issues, their financial and legal status. Through their activities, the society received information on the status of primary schoolThe article highlights the problems of the teachers' congress of teachers for public schools in Ukraine at the end of the XX century